2016
DOI: 10.5811/westjem.2016.6.29948
|View full text |Cite
|
Sign up to set email alerts
|

Does Pneumatic Tube System Transport Contribute to Hemolysis in ED Blood Samples?

Abstract: IntroductionOur goal was to determine if the hemolysis among blood samples obtained in an emergency department and then sent to the laboratory in a pneumatic tube system was different from those in samples that were hand-carried.MethodsThe hemolysis index is measured on all samples submitted for potassium analysis. We queried our hospital laboratory database system (SunQuest®) for potassium results for specimens obtained between January 2014 and July 2014. From facility maintenance records, we identified perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Several papers describe how PTS may increase the risk of in vitro hemolysis [2,[8][9][10]. Clinical chemistry analyses are most often discussed in this context; however, blood gas, hematology and coagulation analyses have also been subject to evaluation when assessing the effects of PTS on specimen integrity [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers describe how PTS may increase the risk of in vitro hemolysis [2,[8][9][10]. Clinical chemistry analyses are most often discussed in this context; however, blood gas, hematology and coagulation analyses have also been subject to evaluation when assessing the effects of PTS on specimen integrity [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that the first primary outcome (the hemolysis rate) did not differ significantly between a PTS and manual transportation. Cakirca and Erdal [10] similarly considered that using a PTS did not significantly affect the hemolysis of blood samples, with hemolysis rates of 8% and 10% in their PTS and manualtransportation groups, respectively; Fernandes et al [21] found corresponding rates of 5.8% and 10%, with no significant difference, as also found by Phelan et al [4]. However, Kara et al [2] found that the hemolysis rate was significantly higher in their PTS group than in their manual-transportation group.…”
Section: Discussionmentioning
confidence: 77%
“…Concerns have been raised that a PTS may cause the hemolysis of blood samples that further results in changes to the levels of potassium (K), lactate dehydrogenase (LDH), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), due to factors such as high pressures, fast transportation speeds, and sudden changes in the transportation direction [2,3]. However, other studies found no relationship between using a PTS and hemolysis [4,5]. These discrepancies have prompted debate about whether using a PTS causes hemolysis, and hospital managers are now hesitating to employ PTSs, instead opting for traditional manual transportation that wastes time and energy.…”
Section: Introductionmentioning
confidence: 99%
“…Since fewer medical staff members are on duty in the nights or holidays, it is a hard work for them to come to the department of transfusion and carry RBCs or PCs to each ward. If the transportation of these products using PTS could be expanded, as has been the case with blood specimens for laboratory tests [12][13][14][15], it might be very helpful for medical staff and lighten their workload.…”
Section: Discussionmentioning
confidence: 99%